Ontologi Pendidikan Di Era Globalisasi Berdasarkan Pandangan Eksistensialisme Jean Paul Sartre - Luqmanul Hakim; Endang Fauziati (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Education in the era of globalization based on the existentialist view of Jean Paul Sartre is an education that prioritizes the freedom of teachers and students in learning. According to Jean Paul Sartre, humans are free creatures. But this freedom must be in accordance with the norms and can be accounted for. Education in the era of globalization has an important role in the formation of student identity, because in the era of globalization, all positive and negative information can be accessed easily, so every human being must be careful in acting. Teachers exist as role models who will become role models for their students both in the classroom and outside the classroom. Existing students are students who are active and creative in learning activities. Students are free to determine the interests and talents of students according to what they like, but this freedom will be the responsibility of students.